Diffuse Alveolar Hemorrhage Associated with Edoxaban Therapy - Kenichi Nitta; Hiroshi Imamura; Akihiro Yashio; Satoko Kashima; Katsunori Mochizuki (Case Reports in Critical Care)
Introduction. The main adverse effect of anticoagulant therapy is bleeding, and major bleeding, including intracranial, gastrointestinal, and retroperitoneal bleeding, has been reported as an adverse effect of edoxaban, a direct oral anticoagulant (DOAC). Bleeding during systemic anticoagulation with edoxaban presents a therapeutic conundrum, because there is currently no safe or efficacious reversal agent to stop major bleeding. Case Report. A 51-year-old woman had multiple traumatic injuries, including lower limb fractures. On day 8, she developed deep venous thrombosis, and edoxaban was administered orally. On day 38, she developed fungemia, which was treated with an antifungal drug. On day 43, she presented with dyspnea. Chest computed tomography scan showed bilateral diffuse ground-glass opacities in the whole lung fields. The results of the subsequent workup (i.e., serum levels of the antineutrophil cytoplasmic antibody, antinuclear antibody, and antiglomerular basement membrane antibody) and microbiological study were unremarkable. Based on these findings, her condition was diagnosed as diffuse alveolar hemorrhage (DAH) associated with edoxaban therapy. The lung opacities disappeared spontaneously after edoxaban therapy was discontinued. Conclusion. DAH is a dangerous complication associated with edoxaban therapy. DOACs, including edoxaban, should be prescribed with caution, especially for patients in a critical condition.